PERANCANGAN SISTEM INFORMASI INVENTORI OBAT E-FARMS BERBASIS WEBSITE DENGAN METODE AGILE - Septa Malan Vergantana; I Wayan Yudik Pradnya (Journal Pharmactive, 2024)
In this research, a website-based E-farms drug inventory system was designed for pharmacies using the Agile method. Website-based e-farms make it easy for officers to search and store drug data online, as well as increasing pharmacy operational efficiency. The Agile method was chosen because of its flexibility and adaptability, as well as its focus on collaboration between the development team and stakeholders. The application of agile development methods (Scrum model) which is iterative, fast, adaptive, and actively involves users in information system development activities, has been proven to be able to produce information systems that suit user needs in a short time. The results of this research are in the form of an inventory information system to handle input data which is then processed to produce output in the form of reports. The design and creation of a computerized web-based Pharmacy Information System is expected to cover all data collection on drug stocks, suppliers, customers and ongoing transactions to make it easier, effective and efficient.